PROSPECTIVE OPPORTUNITIES IN INNOVATIVE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS - Tuychieva, Nodira (MMIT Proceedings, 2023)
The article considers the methods of development of university research, the problems of managing the innovative development of the science of institutions, the specifics of innovative activity in higher educational institutions, approaches to management, and implementation of innovations. Innovations in the educational process should be considered as the introduction of new things into the content of education, which makes significant changes in the nature of the cognitive activity and thinking styles of students and forms their innovative competencies. If the innovator is the leader. The situation is characterized in a special way when an innovator is a head - the director of the school or his deputy, as well as a representative of another level of management. In this case, it is necessary to foresee possible types of reactions from subordinates to innovative actions coming from the leader.